2016
DOI: 10.4103/0366-6999.184458
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasound-guided Transbronchial Needle Aspiration versus Standard Bronchoscopic Modalities for Diagnosis of Sarcoidosis

Abstract: Background:Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is an effective technique used to precisely detect enlarged mediastinal lymph nodes. The efficacy of EBUS-TBNA versus standard modalities for the diagnosis of sarcoidosis remains to be elucidated. In this meta-analysis, we compared the efficacies of these methods.Methods:We searched PubMed, Embase, The Cochrane Library, Wanfang, Cpvip, CNKI, and the bibliographies of the relevant references. We analyzed the data obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The committee also agreed that costs are typically lower for procedures such as EBUS that are performed in an endoscopy room compared with an operating room for mediastinoscopy, and that EBUS is better tolerated than mediastinoscopy because general anesthesia may be avoided (74,75), although the committee acknowledged that dissenting opinions exist (76,77). Finally, the committee noted the ease of adding transbronchial biopsy when lymphadenopathy is accompanied by radiographic findings of parenchymal disease, or endobronchial biopsy when mucosal abnormalities are noted during endoscopy, which further increase the yield of bronchoscopy with EBUS (78). The committee concluded that the advantages of EBUS-guided lymph node sampling for the 87% of patients in whom it is diagnostic outweigh the additional risks and burdens to the 13% of patients who require an additional sampling procedure.…”
Section: Histopathologymentioning
confidence: 99%
“…The committee also agreed that costs are typically lower for procedures such as EBUS that are performed in an endoscopy room compared with an operating room for mediastinoscopy, and that EBUS is better tolerated than mediastinoscopy because general anesthesia may be avoided (74,75), although the committee acknowledged that dissenting opinions exist (76,77). Finally, the committee noted the ease of adding transbronchial biopsy when lymphadenopathy is accompanied by radiographic findings of parenchymal disease, or endobronchial biopsy when mucosal abnormalities are noted during endoscopy, which further increase the yield of bronchoscopy with EBUS (78). The committee concluded that the advantages of EBUS-guided lymph node sampling for the 87% of patients in whom it is diagnostic outweigh the additional risks and burdens to the 13% of patients who require an additional sampling procedure.…”
Section: Histopathologymentioning
confidence: 99%
“…These include bronchoalveolar lavage, endobronchial biopsy, transbronchial lung biopsy, cryobiopsy, and endobronchial ultrasound fine-needle aspiration. These tests are complementary and the combination of tests is superior to performing any single test [24,25]. Although bronchoscopy is often performed in patients with pulmonary disease, a recent study among patients presenting with manifestations of suspected cardiac sarcoidosis without a prior history of lung disease demonstrated that lung and mediastinal lymph node biopsies confirmed extracardiac sarcoidosis in 58% of patients, and bronchoalveolar lavage cellular analyses were suggestive of extracardiac sarcoidosis in 67% of patients, even those without abnormalities on preliminary HRCT [26].…”
Section: Diagnostic Approach To Neurosarcoidosismentioning
confidence: 99%
“…However, in a randomized controlled trial including 130 patients, EBUS-TBNA showed a higher diagnostic yield (74.5%) than did TBNA (48.4%) and EBB (36.3%), with no significant difference from TBLB (69.6%). A meta-analysis of studies including 1823 patients with sarcoidosis compared the diagnostic yield of EBUS-TBNA with that of TBLB and found odds ratios of 0.26 and 126.58, respectively [16]. Finally, EUS-FNA and transbronchial lung cryobiopsy showed no significant difference in the diagnostic yield (66.7%), with a combination of the two modalities increasing the diagnostic yield to 100% [17].…”
Section: Main Textmentioning
confidence: 99%